Trade and Development Report, 1995 - United Nations; United Nations Conference on Trade and Development (New York United Nations, 1995)
The books aims to examine the impact of current international economic issues on the economies of developing countries. It does so by comparing current economic performance with that of the preceding year, by examining future economic prospects, both for the world economy as a whole and for the different regions.
osc 29/06/2016
Loans
Keywords: International trade; Economic Development